Get rolling the beginner's guide to in-line skating - Miller, Liz (Ragged Mountain Press, 1998)
The completely updated and revised edition of the book that the International In-Line Skating Association used to develop its own Level 1 Certification Program, Get Rolling is as essential to novice rollerbladers as a helmet and knee guards. Complemented by a wealth of instructive illustrations, a series of structured lessons and drills enables you to develop a skill fully before moving on. Miller also discusses physical requirements, safety, gear, and equipment maintenance. The book concludes with a list of additional resources.